Thermal stability of additively manufactured austenitic 304L ODS alloy. (30th August 2021) - Ghayoor, Milad; Mirzababaei, Saereh; Sittiho, Anumat; Charit, Indrajit; Paul, Brian K.; Pasebani, Somayeh
Graphical abstract: Highlights: Aging the LPBF 304L ODS alloy at 1200 °C for 100 h did not significantly alter the microstructure. Nanoparticles coarsened to 50 ± 15 nm after holding 100 h at 1200 °C. The LPBF 304L ODS alloy showed a comparable tensile properties with conventionally manufactured ODS alloys. The creep rates were found to be about two orders of magnitude lower than for 304 stainless steel. Abstract: Thermal stability and high-temperature mechanical properties of a 304L austenitic oxide dispersion strengthened (ODS) alloy manufactured via laser powder bed fusion (LPBF) are examined in this work. Additively manufactured 304L ODS alloy samples were aged at temperatures of 1000, 1100, and 1200 °C for 100 h in an argon atmosphere. Microstructure characterization of LPBF 304L ODS alloy before and after the thermal stability experiments revealed that despite the annihilation of dislocations, induced cellular substructure by the LPBF process was partially retained in the ODS alloy even after aging at 1200 °C. The size of Y-Si-O nanoparticles after aging at 1200 °C increased from 25 to 50 nm. EBSD analysis revealed that nanoparticles retained the microstructure of LPBF 304L ODS and hindered recrystallization and further grain growth. At 600 °C and 800 °C, the yield stress of the 290 and 145 MPa were measured, respectively, which are substantially higher than 113 MPa, and 68 MPa for 304L at the same temperatures. Furthermore, the creep properties of LPBF 304L ODS alloy were evaluated at a temperature of 700 °C under three applied stresses of 70, 85, and 100 MPa yielding a stress exponent ( n ) of ∼7.7; the minimum creep rate at 100 MPa was found to be about two orders of magnitude lower than found in the literature for wrought 304L stainless steel.